2010
DOI: 10.1038/cdd.2009.220
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 impairment of apoptotic signaling in macrophages: implication of the PI3K/Akt and the ERK/Nrf-2 defense pathways

Abstract: Lipoxin A 4 (LXA 4 ) is an endogenous lipid mediator that requires transcellular metabolic traffic for its synthesis. The targets of LXA 4 on neutrophils are well described, contributing to attenuation of inflammation. However, effects of lipoxins on macrophage are less known, particularly the action of LXA 4 on the regulation of apoptosis of these cells. Our data show that pretreatment of human or murine macrophages with LXA 4 at the concentrations prevailing in the course of resolution of inflammation (nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 41 publications
6
73
0
Order By: Relevance
“…1B). In agreement with previous data (22) and in part due to the attenuation of the LPS-dependent activation, treatment of BMDM with e-LXA 4 protected against apoptosis (Fig. 1C).…”
Section: Macrophage Profiling Upon Activationsupporting
confidence: 81%
See 2 more Smart Citations
“…1B). In agreement with previous data (22) and in part due to the attenuation of the LPS-dependent activation, treatment of BMDM with e-LXA 4 protected against apoptosis (Fig. 1C).…”
Section: Macrophage Profiling Upon Activationsupporting
confidence: 81%
“…1E). In agreement with this anti-inflammatory pattern (22), a decrease in the expression of NOS-2 and COX-2 and a moderate expression of HO-1 (an Nrf2-dependent gene) at 10 h after e-LXA 4 /LPS challenge was observed (Fig. 1F).…”
Section: Macrophage Profiling Upon Activationsupporting
confidence: 64%
See 1 more Smart Citation
“…This indicates that BML‐111 increases CD163 + cells through a different mechanism than IL‐4 or IL‐10 stimulation, such as direct stimulation on the cells and bypassing cytokine stimulation entirely. This possibility is supported by the fact that both microglia and macrophages express the receptor ALX, and previous studies have shown direct effects of LXA 4 on macrophages to promote debris clearance, inhibit apoptosis, and activate pro‐resolution pathways (Godson et al., 2000; Prieto et al., 2010). Much of what we know of the phenotypes of microglia and macrophages are from in vitro experiments, which do not accurately convey the complexity of an in vivo system, especially one with injury.…”
Section: Discussionmentioning
confidence: 99%
“…51 In contrast, Prieto et al found that pretreatment with LXA 4 promoted a rapid activation of ERK after staurosporine challenge in RAW 264.7 cells. 52 These differences were probably a consequence of signaling convergence and cross-talk between the AKT and ERK cascades.…”
Section: Discussionmentioning
confidence: 99%